From the mixed-up files of mrs. basil e. frankweiler eaudiobook - Konigsburg, E.L (Simon & Schuster Audio, 2009)
A Time Best YA Book of All Time (2021) Run away to the Metropolitan Museum of Art with E. L. Konigsburg's beloved classic and Newbery Medal–winning novel From the Mixed-Up Files of Mrs. Basil E. Frankweiler. When Claudia decided to run away, she planned very carefully. She would be gone just long enough to teach her parents a lesson in Claudia appreciation. And she would go in comfort-she would live at the Metropolitan Museum of Art. She saved her money, and she invited her brother Jamie to go, mostly because be was a miser and would have money. Claudia was a good organizer and Jamie bad some ideas, too; so the two took up residence at the museum right on schedule. But once the fun of settling in was over, Claudia had two unexpected problems: She felt just the same, and she wanted to feel different; and she found a statue at the Museum so beautiful she could not go home until she bad discovered its maker, a question that baffled the experts, too. The former owner of the statue was Mrs. Basil E. Frankweiler. Without her—well, without her, Claudia might never have found a way to go home.